Nerve and tendon approximator - (:unkn) unknown (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 1997)
A practical and simple approximating device, made from a plastic syringe and 2 needles, is described. It allows a safe, tension-free approximation of severed ends of nerves or tendons.